Strategi Pengembangan Objek Wisata Danau Anak Laut Guna Meningkatkan Minat Pengunjung di Desa Gosong Telaga Barat Kecamatan Singkil Utara Kabupaten Aceh Singkil - Putra Bancin; Roida Lumbantobing; Hanna Dewi Aritonang; Mery Silalahi; Ade Putera Arif Panjaitan (Universitas Katolik Widya Karya Malang, 2023)
Each region must have a strategy for developing tourist attractions, this is used to realize progress in increasing tourist interest, such as Gosong Telaga Barat Village in North Singkil District which has the Lake Anak Laut tourist attraction. This research aims to describe the tourist attraction development strategy carried out by the village government for Lake Anak Laut tourism to increase visitor interest in Gosong Telaga Barat Village, North Singkil District. The method used in this research is a qualitative method that describes the subjects and objects studied from the strategy for developing the Lake Anak Laut tourist attraction in Gosong Telaga Barat Village, North Singkil District. The results of this research show that the village government's strategy in developing the Lake Anak Laut tourist attraction is to procure funds and land, build facilities and infrastructure, promote the tourist attraction, and preserve the environmental sustainability of the Lake Anak Laut tourist attraction. Meanwhile, the obstacles are the difficulty of procuring funds from the village budget and the lack of support from the tourism office and district government in the form of budget funds.